The Natural History of Hearing Disorders in Asymptomatic Congenital Cytomegalovirus Infection - Salomè, Serena; Giannattasio, Antonietta; Malesci, Rita; Marciano, Elio; Dolce, Pasquale; Portella, Giuseppe; Continisio, Grazia Isabella; Di Costanzo, Pasquale; Capone, Eleonora; Coppola, Clara; Capasso, Letizia; Raimondi, Francesco (Frontiers in Pediatrics, 2020)
Background and aim: Cytomegalovirus (CMV) is the main cause of congenital infection in developed countries leading to deafness but the burden of sensorineural hearing loss (SNHL) in asymptomatic children remains incompletely characterized. Aim of this study was to evaluate the long-term audiological outcome in this group of patients. Methods: Consecutive neonates with congenital CMV infection were followed from 2002 to 2018. Patients were considered asymptomatic if free from any clinical and instrumental impairment at referral and underwent serial clinical exams, audiological evaluations and CMV-PCR determinations. Results: A cohort of 258 children was analyzed and the disease onset was asymptomatic in 125 (48%) infants. Among these, we studied 102 patients with a follow-up longer than one year and a median observation period of 3.3 years (range: 1 to 10.3 years). No patient developed a stable delayed SNHL but only 14 (14%) presented a variable hearing impairment, 7 of which bilateral. The unstable SNHL was mild in 12 infants and moderate in two. Patients with fluctuating SNHL had significantly higher urine viral load (p 0.002) and more often positive viremia (p 0.015) than babies with stable normal hearing. Conclusions: CMV infected, asymptomatic neonates have a low risk of transient SNHL later in infancy. Positive viremia and high urine viral load at onset are significant risk factors for delayed fluctuating SNHL. These data are relevant for an appropriate follow up plan of these patients.